Energy Harvesters: Hybrid Energy Harvesters: Toward Sustainable Energy Harvesting (Adv. Mater. 34/2019). Issue 34 (20th August 2019) - Ryu, Hanjun; Yoon, Hong‐Joon; Kim, Sang‐Woo
Abstract : In article number1802898, Sang‐Woo Kim and co‐workers summarize the recent progress in hybrid energy harvesters for sustainable energy harvesting. In order to sustainably harvest mechanical, thermal, and solar energy from natural and artificial energy sources, a variety of flexible and stretchable nanogenerators have been developed and hybridized using a variety of materials and structures.